Biophysical drivers of seasonal variability in Sphagnum gross primary production in a northern temperate bog. Issue 5 (6th May 2017) - Walker, Anthony P.; Carter, Kelsey R.; Gu, Lianhong; Hanson, Paul J.; Malhotra, Avni; Norby, Richard J.; Sebestyen, Stephen D.; Wullschleger, Stan D.; Weston, David J.
Abstract: Sphagnum mosses are the keystone species of peatland ecosystems. With rapid rates of climate change occurring in high latitudes, vast reservoirs of carbon accumulated over millennia in peatland ecosystems are potentially vulnerable to rising temperature and changing precipitation. We investigate the seasonal drivers of Sphagnum gross primary production (GPP)—the entry point of carbon into wetland ecosystems. Continuous flux measurements and flux partitioning show a seasonal cycle of Sphagnum GPP that peaked in the late summer, well after the peak in photosynthetically active radiation. Wavelet analysis showed that water table height was the key driver of weekly variation in Sphagnum GPP in the early summer and that temperature was the primary driver of GPP in the late summer and autumn. Flux partitioning and a process‐based model of Sphagnum photosynthesis demonstrated the likelihood of seasonally dynamic maximum rates of photosynthesis and a logistic relationship between the water table and photosynthesizing tissue area when the water table was at the Sphagnum surface. The model also suggested that variability in internal resistance to CO2 transport, a function of Sphagnum water content, had minimal effect on GPP. To accurately model Sphagnum GPP, we recommend the following: (1) understanding seasonal photosynthetic trait variation and its triggers in Sphagnum ; (2) characterizing the interaction of Sphagnum photosynthesizing tissue area with water table height; (3) modeling Sphagnum as a "soil" layer for consistent simulation of water dynamics; and (4) measurement of Sphagnum "canopy" properties: extinction coefficient ( k ), clumping (Ω), and maximum stem area index (SAI). Key Points: Wavelet analysis and mechanistic modeling were applied to Sphagnum GPP calculated from NEE measured in situ at the Marcell Forest, Minnesota, USA Peak GPP was delayed relative to peak photosynthetically active radiation An interaction of the water table with Sphagnum photosynthesizing tissue area was the likely cause of delayed peak GPP